A cross-sectional study of hyponatraemia among elderly patients with heart failure in Uganda. Issue 5 (17th May 2016) - Nankabirwa, Harriet; Kalyesubula, Robert; Ssinabulya, Isaac; Katabira, Elly T; Cumming, Robert G
Abstract : Background: Hyponatraemia is a common electrolyte disturbance among older patients. We determined the prevalence of and factors associated with hyponatraemia among older patients with predominantly acute decompensated heart failure attending a tertiary hospital in Kampala, Uganda. Objectives: Main study aim: (1) to determine the prevalence of hyponatraemia among patients aged 60 years and above with heart failure attending Mulago National Referral Hospital; (2) to describe the factors associated with hyponatraemia among patients aged 60 years and above with heart failure attending Mulago National Referral Hospital. Setting: The study was conducted in one tertiary hospital located in the northeast of Kampala, Uganda. Participants: 400 adults aged 60 years and above were identified for the study. Of these, 188 were excluded as they did not fulfil the inclusion criteria and one declined to participate, leaving a final study group of 211 older adults aged 60 years and above, with a clinical diagnosis of heart failure using Framingham's criteria. Results: The prevalence of hyponatraemia was 24.2% (51/211). Hyponatraemia was mainly found in patients with mild-to-moderate heart failure, New York Heart Association classes 2 and 3. Of the 51 patients with hyponatraemia, 27 (52.9%) had mild hyponatraemia, while 24 (47.1%) had moderate to severe hyponatraemia of 130–125 mmol/L. History of vomiting (OR=2.94, 95% CI 1.29 to 6.70, p=0.010) and use of loop diuretics (OR=2.71, 95% CI 1.13 to 6.52, p=0.026) were identified as independent factors associated with hyponatraemia among older patients with heart failure. Conclusions: Our study revealed a relatively high prevalence of hyponatraemia among older patients with mild to moderate heart failure. Patients presenting with a history of vomiting from any cause or use of loop diuretics were more likely to have hyponatraemia.